An Ayurvedic Approach To Public Health - Kumar, Suresh; Kumar, Ravi; Sharma, Manish Kumar; Patel, Shekhar (International Research Journal of Ayurveda & Yoga, 2020)
It is believed to Ayurveda has existed since the creation of the universe. It is more clearly the science of life because it describes not only the treatment of disease but also the methods of prevention from disease. In today’s era, it has become very difficult to build a healthy society, first of all, to save a person from diseases. Then if there is any disease, treat it and also live a long life. Public health can be obtained from Ayurveda due to both Ayurveda and public health being the same aims. The present article tries to analyze the concept of public health and health brief in the context of Ayurveda. Public health as health is primarily seen as a uniform or a stream for community medicine. The classical texts of Ayurveda describe many theories such as infectious diseases, immunity, nutrition, etc. But the current documents will focus briefly on the concept of public health and health. In the present article, we will try to know whether we can fulfill the purpose of Public Health through Ayurveda.